2016
DOI: 10.1002/erv.2490
|View full text |Cite
|
Sign up to set email alerts
|

Expressed Emotions and Depressive Symptoms in Caregivers of Adolescents with First‐Onset Anorexia Nervosa—A Long‐Term Investigation over 2.5 Years

Abstract: Caregivers of adolescent AN patients suffer from elevated levels of EE and DS. Further studies are needed to examine whether therapeutic interventions to reduce caregivers' EE and DS might have a positive influence on treatment outcome. Copyright © 2016 John Wiley & Sons, Ltd and Eating Disorders Association.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 39 publications
3
14
2
Order By: Relevance
“…CC and EOI scores tended to be higher for mothers than for fathers, albeit these results did not reach statistical significance due to the small number of fathers included in this study. This is not fully in line with several previous reports describing mothers to be more overinvolved than fathers [5,9,43] and fathers to be more critical than mothers [5,43].…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…CC and EOI scores tended to be higher for mothers than for fathers, albeit these results did not reach statistical significance due to the small number of fathers included in this study. This is not fully in line with several previous reports describing mothers to be more overinvolved than fathers [5,9,43] and fathers to be more critical than mothers [5,43].…”
Section: Discussioncontrasting
confidence: 63%
“…High AN symptom impact on caregivers, depression in caregivers, higher psychological distress, higher motivation to change in caregivers, and less caregiver skills accounted for over 60% of the variance of EOI. Other studies also found associations of high EE with psychological distress or depression [1,43,44]. Caregivers' distress and self-care should therefore be the core elements in interventions for caregivers, beside emotion regulation strategies and communication skills.…”
Section: Discussionmentioning
confidence: 92%
“…Due to the complexity of these diseases and the age range in which they appear, there are profound family and social disturbances (Striegel Weissman & Rosselli, 2017). These have an intense effect on family members (Martin et al, 2015;Rhind et al, 2016); many of whom develop anxiety and depression (Schwarte et al, 2017;Sepúlveda et al, 2012). This negative impact is not limited to adolescence but persists into adulthood (Ametller, Castro, Serrano, Martínez, & Toro, 2005;Munsch et al, 2017;Soler et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Family members of patients with anorexia nervosa, especially those with a chronic course, experience high levels of distress and burden and often suffer from mental disorders themselves [35]. The group of Treasure and Schmidt in London developed a skills training intervention programme comprising a book, DVDs and five telephone calls for caregivers [experienced caregivers helping others (ECHO)] and conducted a pragmatic RCT.…”
Section: Psychological Approachesmentioning
confidence: 99%